Cyclosporine 0.05% Ophthalmic Emulsion for Dry Eye in Korea: A Prospective, Multicenter, Open-Label, Surveillance Study - Byun, Yong-Soo (The Korean Ophthalmological Society, 2011)
PURPOSE: To assess the effectiveness and tolerability of cyclosporine ophthalmic emulsion (CsA) 0.05% in patients with moderate to severe dry eye disease in Korea. METHODS: This was a prospective, multicenter, open-label, surveillance study of 392 Korean patients with moderate to severe dry eye disease who were treated with CsA 0.05% for three months. An assessment of effectiveness was performed at baseline, and after 1, 2, and 3 months. The primary effectiveness outcomes were changes in ocular symptoms and Schirmer score. The secondary effectiveness outcomes were a change in conjunctival staining, use of artificial tears, global evaluation of treatment, and patient satisfaction. The primary safety outcome was the incidence and nature of adverse events. RESULTS: A total of 362 patients completed the study. After three months, all ocular symptom scores were significantly reduced compared to the baseline values, while the Schirmer scores were significantly increased relative to baseline (p < 0.0001). After three months, there were significant reductions from baseline in conjunctival staining (p < 0.01) and use of artificial tears (p < 0.0001). According to clinicians' global evaluations, most patients (>50%) experienced at least a 25% to 50% improvement in symptoms from baseline at each follow-up visit. The majority of patients (72.0%) were satisfied with the treatment results, and 57.2% reported having no or mild symptoms after treatment. The most common adverse events were ocular pain (11.0%). CONCLUSIONS: Our findings indicate that CsA 0.05% is an effective and tolerable treatment for dry eye disease in Korean clinical practice.